Abe : Abraham Lincoln in his times - Reynolds, David S., 1948- (Penguin Press, 2020)
"ABE is a cultural biography of Abraham Lincoln, following Lincoln's monumental life from cradle to grave while weaving a narrative that includes Lincoln's cultural influences and the nation-wide and regional cultural trends and moods and happenings of his day, and how Lincoln both shaped and was shaped by his America. The music, humor, literature, and fashions of the time and their impact on Lincoln's life are explored as well, and analysis of other important figures such as Lincoln's wife, his assassin, his professional partners, etc., also draw on this culturally focused style"--